2022
DOI: 10.1186/s13071-022-05363-y
|View full text |Cite
|
Sign up to set email alerts
|

The IMD and Toll canonical immune pathways of Triatoma pallidipennis are preferentially activated by Gram-negative and Gram-positive bacteria, respectively, but cross-activation also occurs

Abstract: Background Antimicrobial peptides (AMPs) participate in the humoral immune response of insects eliminating invasive microorganisms. The immune deficiency pathway (IMD) and Toll are the main pathways by which the synthesis of these molecules is regulated in response to Gram-negative (IMD pathway) or Gram-positive (Toll pathway) bacteria. Various pattern-recognition receptors (PRRs) participate in the recognition of microorganisms, such as pgrp-lc and toll, which trigger signaling cascades and ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 50 publications
(65 reference statements)
0
13
0
Order By: Relevance
“…The induction of the core elements of the Jak/Stat pathway ( Supplementary Figure S2D ) is concordant with ChIP data targeting Dorsal (Dl), which indicates that Dl binds the promoters of all Jak/Stat core components (30). The response to Gram-negative bacteria is commonly associated with the activation of the IMD pathway and illustrates the cross-talk between the Toll and the IMD pathways (31-34). Most core components of the IMD pathways as well as the majority of anti-microbial peptides are upregulated in gcm 26 /+;Toll 10b /+ compared to gcm 26 /+ ( Figure 2A’-A’’’ , B ), suggesting that the Toll pathway may activate the IMD pathway.…”
Section: Resultsmentioning
confidence: 99%
“…The induction of the core elements of the Jak/Stat pathway ( Supplementary Figure S2D ) is concordant with ChIP data targeting Dorsal (Dl), which indicates that Dl binds the promoters of all Jak/Stat core components (30). The response to Gram-negative bacteria is commonly associated with the activation of the IMD pathway and illustrates the cross-talk between the Toll and the IMD pathways (31-34). Most core components of the IMD pathways as well as the majority of anti-microbial peptides are upregulated in gcm 26 /+;Toll 10b /+ compared to gcm 26 /+ ( Figure 2A’-A’’’ , B ), suggesting that the Toll pathway may activate the IMD pathway.…”
Section: Resultsmentioning
confidence: 99%
“…These target DEmRNAs were involved in six cellular immune pathways, such as apoptosis, melanogenesis, endocytosis, autophagy-animal, apoptosis -fly, and insect hormone biosynthesis (Figure 8A). Toll, IMD, and JAK/STAT are three vital signaling pathways, among which, the Toll signaling pathway mainly responds to Gram-positive and fungal infestations, while the IMD signaling pathway mainly responds to Gram-negative infestations [76]. The JAK/STAT signaling pathway is mainly involved in antiviral natural immunity and melanism [77].…”
Section: Discussionmentioning
confidence: 99%
“…Most research on triatomines has been carried out on R. prolixus and considerable progress in understanding the complex interaction of T. cruzi with the insect vector is being made [ 4 , 24 , 135 , 136 , 137 , 138 , 139 ]. Phagocytosis by the haemocytes in Rhodnius has been described following T. rangeli invasion from the gut into the haemolymph and following injection of bacteria into the haemolymph [ 140 ].…”
Section: Vector Cellular Immunitymentioning
confidence: 99%
“…36% for E. coli and 41% for Micrococcus luteus after silencing both pathways. This indicated that the Imd and Toll pathways participate jointly to eliminate Gram+ and Gram− bacteria [ 139 ]. Challenging with T. cruzi or T. rangeli and monitoring parasite numbers might have yielded interesting results regarding the participation of the Imd and Toll pathways in immune reactions towards parasites.…”
Section: Vector Humoral Immunitymentioning
confidence: 99%